Kecukupan Konsumsi Pangan Hewani di Kota Jambi dalam Hubungannya Kualitas Sumberdaya Manusia Keluarga Serta Faktor-Faktor Yang Mempengaruhinya - Farhan, Muhammad (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
This  research  was  aimed  to  1)  determine the  sufficiency  of  animal  food  consumption  such  as amount  of  food  consumption,  animal  protein  and  energi  consumption  for  the  healthy  life,  2)    find  the correlation  between  sufficincy  of  animal  food  consumptionand  human  resources  quality  and,  3) determine family member appetite on  animal food consumption, food accessibility, income per capita, 4) find the  correlation between animal food availability in their house hold to the sufficiency of animal food consumption  .  the  research  was  condcted  by  survey  in  2 steps  namely  discriptive  and  representative steps.  Sample  were  collected  by  multi  stage  cluster  random  sampling  and  sample  size  were  fixed  by iteratif  methode  .  Correlation  and  patway  abalysis  were  used  as  analysis  model.  This    study  concluded that ; 1) Animal food consumption  in Jambi regency was still under animal food consumption standard, 2) More sufficient animal food consumption  did not inprove quality of human resorces of family member, 3)  Sosisal  culture  and  economic  condition  of  the  family  and  animal  food  availability  at  the  house  hold level had significant food consumption, animal protein and energy